Learning-by-Exporting Effects : Are They for Real? - Fernandes, Ana M. (Taylor and Francis, 2015)
In this article, the authors thoroughly examine the learning-by-exporting (LBE) hypothesis for Colombian manufacturing plants during 1981–91 and find significant evidence in its favor. The results are robust to the use of different samples of the data set, different econometric methods, and different modeling approaches. The authors find that export experience acquired by plants in years before the previous year has an important effect on plant productivity and that the effect of export experience on productivity is nonsignificant for exporters that stopped exporting in the previous year. There is also evidence of diminishing returns to export experience in that LBE effects are quantitatively lower for the experienced exporters in the sample.